2020
DOI: 10.1016/j.joca.2020.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of 12 weeks of supervised treatment compared to written advice in patients with knee osteoarthritis: a secondary analysis of the 2-year outcome from a randomized trial

Abstract: Objective: To assess the 24-month cost-effectiveness of supervised treatment compared to written advice in knee osteoarthritis (OA). Design: 100 adults with moderate-severe OA not eligible for total knee replacement (TKR) randomized to a 12-week individualized, supervised treatment (exercise, education, diet, insoles and pain medication) or written advice. Effectiveness was measured as change in quality-adjusted life years (QALYs) from baseline to 24 months, including data from baseline, 3, 6, 12 and 24 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…38 39 Limitations Given that the 95% CI (−1.5 to 12.1) of the main outcome KOOS 4 and 3 out of 5 KOOS subscales included the minimal clinically important difference (10 points), the true difference in change between groups could potentially be clinically relevant in favour of the nonsurgical treatment group. While a 2-year analyses of the study demonstrated that the MEDIC treatment was costeffective as compared with written advice, 40 the 5-year cost-effectiveness is unknown. The improvements from baseline to 5 years in both treatment groups could be influenced by regression towards the mean, that is, patients originally sought medical care when their symptoms were most intolerable.…”
Section: Discussionmentioning
confidence: 97%
“…38 39 Limitations Given that the 95% CI (−1.5 to 12.1) of the main outcome KOOS 4 and 3 out of 5 KOOS subscales included the minimal clinically important difference (10 points), the true difference in change between groups could potentially be clinically relevant in favour of the nonsurgical treatment group. While a 2-year analyses of the study demonstrated that the MEDIC treatment was costeffective as compared with written advice, 40 the 5-year cost-effectiveness is unknown. The improvements from baseline to 5 years in both treatment groups could be influenced by regression towards the mean, that is, patients originally sought medical care when their symptoms were most intolerable.…”
Section: Discussionmentioning
confidence: 97%
“…Guidelines [ [8] , [9] , [10] ] recommend patient education, exercise-therapy and weight management where indicated as first-line care for knee osteoarthritis. Patient education and exercise-therapy are cost-effective [ 11 , 12 ], can avert surgery [ 13 , 14 ] and have compelling evidence of effectiveness including moderate pain and function improvements compared to control interventions, regardless of radiographic or pain severity [ [15] , [16] , [17] ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous analyses of the GLA:D programme, but with twice the number of supervised neuromuscular exercise sessions, weight loss, insoles and pain medication if needed, have found similar results. 15 31 A model-based study suggested that exercise therapy and education was cost-effective as compared with usual care for patients with knee or hip OA in Canada, 31 while an analysis of results from a randomised trial comparing supervised exercise therapy, education and other recommended non-surgical interventions to written advice in patients with moderate to severe knee OA found the intervention to be cost-effective with incremental cost effectiveness ratios of 6229 to 20 688€/QALY. 15 Even though our study is a pre–post study and therefore not directly comparable, our findings are also in line with other previous studies which have indicated that supervised exercise therapy alone as treatment for OA is cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“… 15 31 A model-based study suggested that exercise therapy and education was cost-effective as compared with usual care for patients with knee or hip OA in Canada, 31 while an analysis of results from a randomised trial comparing supervised exercise therapy, education and other recommended non-surgical interventions to written advice in patients with moderate to severe knee OA found the intervention to be cost-effective with incremental cost effectiveness ratios of 6229 to 20 688€/QALY. 15 Even though our study is a pre–post study and therefore not directly comparable, our findings are also in line with other previous studies which have indicated that supervised exercise therapy alone as treatment for OA is cost-effective. Three randomised trials demonstrated that supervised exercise therapy in addition to usual care, supplementary class-based exercise in addition to a home-based programme and supervised exercise therapy compared with general practitioner care alone was likely to be cost-effective in people with knee and/or hip OA.…”
Section: Discussionmentioning
confidence: 99%